Pemberdayaan Melalui Edukasi Kewirausahaan Dan Pembukuan Keuangan Bagi UKM Gerai Kopimi Kelurahan Mlatiharjo Semarang - C Tri Widiastuti; Nuria Universari; Rr. Lulus Prapti N.S.S (Universitas Negeri Gorontalo, 2023)
Community service for Gerai Kopimi UKM in the Kelurahan Mlatiharjo Semarang focuses on providing counseling on entrepreneurship, financial management, and simple bookkeeping to increase knowledge, creativity, and innovation so they can produce unique products, increase profits and maintain business continuity. According to the problems faced by partners, namely 1) The lack of knowledge about entrepreneurship properly. 2) The problem of weak human resources regarding financial knowledge, especially related to financial management. 3) weak business management, especially the rules for recording/bookkeeping. 4) The lack of business actors accessing government policies in small business development programs. Methods of this activity include discussions, training, business management support, and simple financial bookkeeping. The results of Community Service activities show that Gerai Kopimi UKM Partners are able to absorb knowledge related to entrepreneurship that is provided properly, understand financial business records, separate personal finances, and finances, and make good decisions for the sustainability of implementation.